Evaluation potency of Boesenbergia rotunda as antioxidant achieved by free radicals scavenging activities - Dinda; Kurnia, Irmayanti Tri; Hariyanto, Nova Alfian; Suwandari, Suhartini; Firdaus, Yazdaniar Fajri Halimi; Mahmuda, Nur Fariha; Phuwapraisirisan, Preecha; Ramadhan, Rico (Universitas Airlangga, 2023)
Boesenbergia rotunda has antioxidant potential to inhibit free radicals. Antioxidant activity was determined by free radical scavenging activity against DPPH, ABTS and Cuprac. The results showed that the hexane extract of Boesenbergia rotunda had a strong percent antioxidant activity with a value of 91.38, while ascorbic acid as a positive control had a value of 99.85. Antioxidant activity test results showed that hexane and dichloromethane extracts have DPPH, ABTS, and cuprac free radical scavenging activities